Analysis of Procurement Routes and Contract Types for Housing Retrofit in the United Kingdom - Chamara Panakaduwa; Paul Coates; Mustapha Munir (Buildings)
The study focused on the procurement routes and the forms of contract, currently used in the UK housing retrofit industry. Importantly, the contracts between the clients and the contractors were investigated. This study used a qualitative approach with a critical literature review and semi-structured interview data collection for the methodology. The findings show that the housing retrofit industry does not use any standard form of contract in general. Most contractors use guarantees, warranties, and invoices instead of standard forms of contract. They usually use bespoke contracts if contract administration is required. This is because there is nothing wrong with the existing way of addressing contract administration in retrofit. As the UK needs to retrofit 30.1 million houses, there can be contractual disputes aggregating to 8.1 million properties or GBP 221.4 billion project value. The study recommends using standard forms of contract to avoid and reduce the detrimental effects of contractual disputes in housing retrofit in the future.